INFLUENCE COMPETENCE, TRANSFORMAS DIGITAL AND UPDATE SKILLS ON EMPLOYEE PERFORMANCE AT DINAS SUMBER DAYA AIR, CIPTA KARYA DAN TATA RUANG PROVINSI SUMATERA UTARA - Biasna Br Bancin; R. Sabrina; Hazmanan Khair; Satria Tirtayasa; Hasrudy Tanjung (Jurnal Ekonomi, 2023)
The purpose of this study was to determine and analyze the effect of employee competence, digital transformation and skills renewal on employee performance At Dinas Sumber Daya Air, Cipta Karya Dan Tata Ruang Provinsi Sumatera Utara on Jalan Sakti Lubis No. 7 Medan. The sample in this study using the formula slovin 10% as many as 70 employees, where the population of all employees as many as 239 employees. Data collection techniques in this study using the questionnaire method and back as many as 70 questionnaire respondents, while data analysis techniques in this study using a quantitative approach with statistical analysis program SEM PLS version 21. The results of this study prove that directly employee competencies have a positive and significant effect on employee performance, directly digital transformation has a positive and significant effect on employee performance, and directly skill renewal (reskilling) has a positive and significant effect on employee performance. Simultaneously, employee competency, digital transformation and reskilling affect employee performance by 71.1%. This calculation provides an explanation that in order to realize good performance and increase, there needs to be improvement and more efforts in increasing competence, using digital transformation and updating skills (reskilling) for workers/employees. This shows that the development of employees through competence, digital transformation, and skills renewal (reskilling) can affect the performance of employees of the Department of Water Resources, Cipta Karya and spatial North Sumatra province in improving employee performance that is effective and efficient and more professional.